2019
DOI: 10.1002/cctc.201901382
|View full text |Cite
|
Sign up to set email alerts
|

Facet‐Dependent Activity of Co3O4 Catalyst for C3H8 Combustion

Abstract: Clarifying the facet‐dependent activity of Co3O4 towards C3H8 combustion is of great importance to have a deep understanding of reaction mechanism and develop highly active Co3O4 based catalysts for light hydrocarbon combustion. In this work, four different Co3O4 nanocatalysts which dominantly exposed {100}, {111}, {110} and {112} facets, respectively, were synthesized via hydrothermal method and further tested in C3H8 combustion. The catalytic activity of different crystal planes varied as the order of {111}>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Mn can be doped into the (100) surfaces of Co 3 O 4 , but cannot be doped into (111) surfaces. [26][27][28] It can be only excessively accumulated on the (111) surfaces. Due to the Mn doping into the (100) surfaces of the Co 3 O 4 , Mn 3+ partially replaces Co 3+ , resulting in lattice expansion.…”
Section: Resultsmentioning
confidence: 99%
“…Mn can be doped into the (100) surfaces of Co 3 O 4 , but cannot be doped into (111) surfaces. [26][27][28] It can be only excessively accumulated on the (111) surfaces. Due to the Mn doping into the (100) surfaces of the Co 3 O 4 , Mn 3+ partially replaces Co 3+ , resulting in lattice expansion.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, Co 3 O 4 was prepared through a solid-state method to reach a propane conversion of 50%, at reaction temperatures higher than 210 °C [ 39 ]. In another work, it was demonstrated that the catalytic activity of Co 3 O 4 catalysts was facet-dependent, reaching 90% conversion at 239 °C in the best cases [ 25 ]. The effect of pH in the synthesis of cobalt oxide has been also studied on the catalytic performance in propane total oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated transition metal oxide catalysts and demonstrated that oxides of manganese [ 16 , 17 , 18 ] or cobalt are also highly active [ 19 , 20 , 21 , 22 , 23 ]. In fact, Co 3 O 4 presents a catalytic activity for total oxidation of alkanes (the least reactive VOCs) comparable or even greater than those of noble metal- based catalysts [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of different crystal planes on metal oxides will lead to great differences in catalytic activity because different facets usually have dissimilar atomic arrangements, electronic structures, and surface active sites. Therefore, the investigation of the crystal facets is not only of great significance to the in-depth study of VOCs degradation mechanism but also can reasonably guide the design and synthesis of high-performance catalysts to meet industrial needs.…”
Section: Design Strategies Of Spinel Catalystmentioning
confidence: 99%